On wave operators for the multidimensional electromagnetic Schrödinger operator in divergent form - Aliev, A. R.; Eyvazov, E. H. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We prove the existence of wave operators for the multidimensional electromagnetic Schr¨odinger operator in divergent form by the Cook method. Moreover, under certain conditions on the coefficients of the given operator, we establish the isometry of its wave operators and determine the initial domains of these operators.